Further analysis of six painted rock fragments collected by Louis Tylor - Hobart, John; Pearce, David (Southern African Humanities, 2010)
This note provides additional details about the six fragments of South African Drakensberg rock paintings collected by Louis Tylor in 1893. It uses new drawings based on tracings to offer some additional comments.